Analysis of futsal matches using a single-camera computer vision system - Paulichen, Heloiza; Zielinski, Kallil; Casanova, Dalcimar; Cavalcanti, Pablo (Anais do Workshop de Visão Computacional (WVC), 2020)
The use of computer systems in sports has increased significantly in the last decade. Consequently, systems have been developed to help each athlete or team quantify their performance, such as distances traveled, speeds attained, and positions where each athlete was on the court or field. In this work, a method based on computer vision is proposed to analyse futsal matches. Videos were acquired using a single camera with a wide-angle lens, which facilitates the installation and calibration process in different matches and arenas. The approach is illustrated through video recordings of Pato Futsal team, from which the athletes were detected, their positions projected from pixels to real world coordinates their trajectories estimated. The generated data visualization aims to help coaches in their physical and tactical analysis.